UPAYA PENINGKATAN HASIL PEMBELAJARAN PRODUK KREATIF DAN KEWIRAUSAHAAN SISWA DENGAN PROYEK MELALUI EXPERIENTIAL MARKETING DAN SOCIAL MEDIA MARKETING DI SMKN 4 SURABAYA - Dr. Finisica Dwijayati Patrikha, S.Pd., M.Pd.; Vania Elvaretta Tiarawati (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
The development of technology and social media has opened new opportunities for strengthening entrepreneurship education in Vocational High Schools (SMK). However, challenges arise from the need for adaptive learning that aligns with the demands of the workplace. On the other hand, government programs supporting students' creative projects need to be utilized optimally. This study aims to describe the role of experiential marketing and social media marketing in improving the outcomes of students' Creative Product and Entrepreneurship (PKK) learning projects at SMKN 4 Surabaya. This study uses a qualitative approach with snowball sampling techniques, involving informants from the school, teachers, mentors, and students. Data was collected through interviews and observations. The results of the study indicate that the implementation of the project-based learning model is effective in encouraging active student involvement through real-world experiences in the production and promotion processes. The experiential marketing approach enhances students' practical skills and conceptual understanding of the business world, while the integration of social media marketing provides students with opportunities to hone their digital marketing skills directly. The combination of these two approaches creates holistic and contextual learning, facilitating the development of entrepreneurial attitudes and products relevant to market needs.